Tailoring the product dstribution with batch and continuous process options in catalytic hydrogenation of furfural - Biradar, Narayan S.; Hengne, Amol A.; Birajdar, Shobha N.; Swami, Rameshwar; Rode, Chandrashekhar V. (Organic Process Research & Development, 2014)
Various noble metal catalysts were screened in a batch operation for a furfural (FFR) single-step decarbonylation and hydrogenation reaction to obtain THF in high selectivity. Among these, the 3% Pd/C showed complete FFR conversion with a total of 80% selectivity to ring hydrogenated products including tetrahydrofuran (THF). The order of activity exhibited by other noble metals was Pt/C > Re/C > Ru/C. Although Pt/C exhibited the highest activity, its decarbonylation and ring hydrogenation ability were the least (24%) with a major product selectivity of 66% to furfuryl alcohol (FAL). Similarly, the Cu catalyst gave almost complete selectivity to FAL. In a continuous operation (23 g catalyst bed), the 3% Pd/C catalyst showed higher selectivity of >40% compared to THF alone with complete FFR conversion and on-stream activity of similar to 100 h. The reaction pathway elucidated from some control experiments revealed that the decarbonylation of FFR to furan over the Pd/C catalyst is a prerequisite for THF formation.

Triple nanocomposites of CoMn2O4, Co3O4 and reduced graphene oxide for oxidation of aromatic alcohols - Jha, Ajay; Mhamane, Dattakumar; Suryawanshi, Anil; Joshi, Sameer M.; Shaikh, Parvez; Biradar, Narayan S.; Ogale, Satishchandra; Rode, Chandrashekhar V. (Catalysis Science & Technology, 2014)
A composite of reduced graphene oxide (RGO) with oxides of manganese and cobalt together was prepared by a solvothermal method. During synthesis, both the reduction of graphene oxide as well as the growth of nanorod shaped CoMn2O4 and Co3O4 occurred simultaneously having a crystallite size of similar to 8 nm calculated from X-ray diffraction (XRD). The as-obtained triple nanocomposite material designated as RGO-MnCoO exhibited excellent activity for the liquid phase aerobic oxidation of aromatic alcohols under base-free conditions selectively giving the corresponding aldehydes (>85%). RGO loading was varied in the range of 1-10%, among which 1% RGO-MnCoO showed maximum catalytic activity enhancement of 24% as compared to the bare mixed oxide (MnCo-MO) for the oxidation of vanillyl alcohol. HR-TEM of RGO-MnCoO revealed that it was a composite material having uniform nanotubes of similar to 25 nm length and 6 nm diameter with a fringe pattern showing the (103) and (004) planes and lattice spaces of 0.26 nm and 0.22 nm, respectively, for the spinel CoMn2O4. The detailed studies on the morphology, size and composition of the as-prepared RGO-MnCoO nanocomposite by XRD, XPS, N-2-adsorption/desorption and O-2-TPD techniques were used to understand the role of RGO in the enhancement of catalytic activity for oxidation reaction.

Transfer hydrogenation of biomass-derived levulinic acid to gamma-valerolactone over supported Ni catalysts - Hengne, Amol M.; Kadu, Brijesh S.; Biradar, Narayan S.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (RSC Advances, 2016)
A sustainable process of catalytic transfer hydrogenation (CTH) of levulinic acid (LA) to gamma-valerolactone (GVL) was investigated over Ni on various supports (Al2O3, ZnO, MMT and SiO2) in the presence of isopropanol (IPA) as the H-donor. Among these, the montmorillonite (MMT) supported Ni catalyst showed almost complete LA conversion (>99%) and selectivity (>99%) to GVL within 1 h. XRD and XPS results showed that the concentration of the metallic species significantly enhanced (two to four times) in the recovered sample as compared to the freshly prepared Ni/MMT. This was due to the in situ reduction of Ni2+ species present on the catalyst surface, through liberated H-2 under the reaction conditions. The strong acid strength of MMT, evidenced by NH3-TPD and py-IR, facilitated the esterification of LA as well as cyclization to GVL. The conversion-selectivity pattern was found to decrease in the IPA-water mixture while, it remained unchanged in the IPA-acetone mixture. Our catalyst could be efficiently recycled up to five times with consistent CTH activity and selectivity to GVL. The plausible mechanism of LA to GVL conversion involves the formation of a levulinate ester with IPA that favours its simultaneous hydrogenation and cyclization in a spontaneous manner to give GVL and regenerating IPA for sustainability.